Pectin Methylesterases Modulate Plant Homogalacturonan Status in Defenses against the Aphid Myzus persicae. Issue 8 (24th May 2019) - Silva-Sanzana, Christian; Celiz-Balboa, Jonathan; Garzo, Elisa; Marcus, Susan E.; Parra-Rojas, Juan Pablo; Rojas, Barbara; Olmedo, Patricio; Rubilar, Miguel A.; Rios, Ignacio; Chorbadjian, Rodrigo A.; Fereres, Alberto; Knox, Paul; et al.
Abstract : The role of homogalacturonan status modulated by PME/PMEI13 is a central component of the early defense responses of Arabidopsis against infestation by the green peach aphid, Myzus persicae . Abstract: Because they suck phloem sap and act as vectors for phytopathogenic viruses, aphids pose a threat to crop yields worldwide. Pectic homogalacturonan (HG) has been described as a defensive element for plants during infections with phytopathogens. However, its role during aphid infestation remains unexplored. Using immunofluorescence assays and biochemical approaches, the HG methylesterification status and associated modifying enzymes during the early stage of Arabidopsis ( Arabidopsis thaliana ) infestation with the green peach aphid ( Myzus persicae ) were analyzed. Additionally, the influence of pectin methylesterase (PME) activity on aphid settling and feeding behavior was evaluated by free choice assays and the Electrical Penetration Graph technique, respectively. Our results revealed that HG status and HG-modifying enzymes are significantly altered during the early stage of the plant-aphid interaction. Aphid infestation induced a significant increase in total PME activity and methanol emissions, concomitant with a decrease in the degree of HG methylesterification. Conversely, inhibition of PME activity led to a significant decrease in the settling and feeding preference of aphids. Furthermore, we demonstrate that the PME inhibitor AtPMEI13 has a defensive role during aphid infestation, since pmei13 mutants are significantly more susceptible to M. persicae in terms of settling preference, phloem access, and phloem sap drainage.